Razvoj jezika in mišljenja pri gluhih otrocih - Pfifer, Ajda (Psihološka obzorja (Ljubljana), 2010)
The article reviews the current studies regarding language and cognitive development in children who are deaf. Deaf communicate orally and with sign language. 90 % of deaf children are born into hearing families and hearing parents in most cases do not know the sign language. Besides, hearing parents usually want for their child to become 'normally' speaking. Most of the deaf children born into hearing families have very poor early communication. It is now well established that deaf children of deaf parents generally exhibit normal patterns of development in social, linguistic and cognitive domains relative to their hearing peers. One of the longest-running debates in the field of deaf education was whether introducing young deaf children to sign language impairs their ability and motivation for learning spoken language. Today we have no evidence supporting the hypothesis of a negative effect of sign language on development of spoken langugage.
Keywords: gluhi; child; otroci; jezikovni razvoj; kognitivni razvoj; znakovni jezik; družinsko okolje; starši